Harnessing the Therapeutic Potential of Extracellular Vesicles for Biomedical Applications Using Multifunctional Magnetic Nanomaterials (Small 13/2022). Issue 13 (1st April 2022) - Yang, Letao; Patel, Kapil D.; Rathnam, Christopher; Thangam, Ramar; Hou, Yannan; Kang, Heemin; Lee, Ki‐Bum
Abstract : Extracellular Vesicles Extracellular vesicles (EVs) combined with multifunctional nanomaterials have rapidly emerged as promising platforms for various biomedical applications. In article number 2104783, Heemin Kang, Ki‐Bum Lee, and co‐workers describe several key challenges and possible nanotechnology‐enabled EV applications, such as next‐generation EV‐based disease diagnosis, drug delivery, tissue engineering, and regenerative medicine.